2022
DOI: 10.1097/cad.0000000000001289
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG11 enhances bevacizumab resistance in colorectal cancer by mediating miR-1207-5p/ABCC1 axis

Abstract: Long noncoding RNAs (lncRNAs) have been reported to serve as vital regulators in the chemoresistance of human cancers, including colorectal cancer (CRC). In this study, we aimed to explore the functions of lncRNA small nucleolar RNA host gene 11 (SNHG11) in the resistance of CRC to bevacizumab. Quantitative real-time PCR, western blot assay or immunohistochemistry assay were performed to examine the expression of SNHG11, microRNA-1207-5p (miR-1207-5p), ATP binding cassette subfamily C member 1 (ABCC1) and Ki67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…By contrast, the exosome-mediated delivery of miR-374a-5p inhibitor suppresses chemoresistance by increasing neuro D1 expression in gastric cancer cells [ 81 ]. The downregulation of SNHG11 induces apoptosis in bevacizumab-resistant CRC cells by targeting miR-1207-5p and decreasing the expression of ABCC1 [ 82 ]. Exosomal circSFMBT2 is highly expressed in the serum of docetaxel-resistant prostate cancer patients [ 83 ].…”
Section: Exosomal Non-coding Rnas As Regulators Of Cancer Progression...mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the exosome-mediated delivery of miR-374a-5p inhibitor suppresses chemoresistance by increasing neuro D1 expression in gastric cancer cells [ 81 ]. The downregulation of SNHG11 induces apoptosis in bevacizumab-resistant CRC cells by targeting miR-1207-5p and decreasing the expression of ABCC1 [ 82 ]. Exosomal circSFMBT2 is highly expressed in the serum of docetaxel-resistant prostate cancer patients [ 83 ].…”
Section: Exosomal Non-coding Rnas As Regulators Of Cancer Progression...mentioning
confidence: 99%
“…In particular, mimics or inhibitors could be used in combination with chemotherapeutic drugs to overcome anticancer drug resistance. Table 2 [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ] and Figure 3 show the roles played by exosomal non-coding RNAs in cancer progression and anticancer drug resistance.…”
Section: Exosomal Non-coding Rnas As Regulators Of Cancer Progression...mentioning
confidence: 99%
“…Several studies have reported the lack of association [ 190 , 192 ], whereas others have observed a link between TNM staging and differentiation grade and enhanced MRP1 expression in CRC biopsies, revealed by positive immunohistochemical staining [ 193 ]. Moreover, in vitro testing has demonstrated that MRP1 is associated with resistance to oxaliplatin, 5-FU, and bevacizumab [ 177 , 178 , 194 ]. Besides, the detection of MRP1 in circulating tumor cells in patients with CRC has recently been suggested as a biomarker of irinotecan resistance [ 179 , 195 ].…”
Section: Colorectal Carcinomamentioning
confidence: 99%
“…The lncRNAs affect cell growth, proliferation, apoptosis, and differentiation 26,27 via epigenetic mechanisms 28,29 . SNHG11, a potential prognostic marker in gastric cancer, 27 colorectal cancer, 30 hepatocellular carcinoma, 31 and prostate cancer, 32 promotes proliferation 33 and migration, 34 thereby suppressing apoptosis, 35 while impacting other cellular functions 36 …”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] The lncRNAs affect cell growth, proliferation, apoptosis, and differentiation 26,27 via epigenetic mechanisms. 28,29 SNHG11, a potential prognostic marker in gastric cancer, 27 colorectal cancer, 30 hepatocellular carcinoma, 31 and prostate cancer, 32 promotes proliferation 33 and migration, 34 thereby suppressing apoptosis, 35 while impacting other cellular functions. 36 In this study, we found a decrease in the expression of SNHG11 in glaucomatous human TM (GTM 3 ) cells compared with immortalized human TM (iHTM) cells, while its role in TM cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%